De integratione fluxionum formae: (sin Z)m. (cos Z)n dZ - Wallenius, Martinus Johannes; Lindqvist, Johannes Henricus; Frenckell, Johan Christopher I (kirjapaino, Turku, 1761-1779); Turun Akatemia; Royal Academy of Turku; Regia Academia Aboensis; Kungliga akademin i Åbo (Aboae : impressit Joh. C. Frenckell, [1768], 1768)
Dedikaatio: Anna Lindqvist född Frendeen [ruots.].
Keywords: matematiikka